Efektivitas Sales Promotion dalam Meningkatkan Repurchase Intention pada Bisnis Ritel - Soviyanti, Ova; Mulyadi, Hari; Wibowo, Lili Adi (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
The purpose of this study is to find out how much influence sales promotion has on repurchase intention. The type of research used is descriptive and verification. The method used in this research is explanatory survey with systematic random sampling technique and the number of respondents is 100 people. The data analysis technique used in this study is simple linear regression with SPSS 21.0 computer software The research findings on hypothesis testing can be seen that sales promotion has a positive influence on repurchase intention. The originality of this research was found in the object of research, research period, measuring instruments and research results. The author also adds theories from foreign journals and foreign books.